What Is Most Suitable for Children With Cystic Fibrosis—The Relationship Between Spirometry, Oscillometry, and Multiple Breath Nitrogen Washout - Postek, Magdalena; Walicka-Serzysko, Katarzyna; Milczewska, Justyna; Sands, Dorota (Frontiers in Pediatrics, 2022)
Introduction In cystic fibrosis (CF), pathological lung changes begin early in life. The technological progress currently gives many diagnostic possibilities. However, pulmonary function testing in children remains problematic. Objectives Our study aimed to correlate the results of impulse oscillometry (IOS) with those of multiple breath nitrogen washout (MBNW) in our pediatric CF population. We also compared those parameters between the groups with and without spirometric features of obturation. Methods We collected 150 pulmonary function test sets, including spirometry, IOS, and MBNW in patients with CF aged 12.08 ± 3.85 years [6–18]. The study group was divided into two subgroups: IA (without obturation) and IB (with obturation). We also compared Sacin, Scond, and oscillometry parameters of 20 patients aged 14–18 years who reached the appropriate tidal volume (VT) during MBNW. Results Statistical analysis showed a negative correlation between lung clearance index (LCI) and spimoetric parameters. Comparison of subgroups IA (n = 102) and IB (n = 48) indicated a statistically significant difference in LCI (p < 0.001) and FEV1z-score (p < 0.001), FEV1% pred (p < 0.001), MEF25z-score (p < 0.001), MEF50 z-score (p < 0.001), MEF75 z-score (p < 0.001), R5% pred (p < 0.05), and R20% pred (p < 0.01). LCI higher than 7.91 was found in 75.33% of the study group, in subgroup IB—91.67%, and IA−67.6%. Conclusions LCI derived from MBNW may be a better tool than IOS for assessing pulmonary function in patients with CF, particularly those who cannot perform spirometry.